2014
DOI: 10.1186/1471-2334-14-208
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and behaviour of hospital health-care workers regarding influenza A/H1N1: a cross sectional survey

Abstract: BackgroundTo assess the knowledge, the attitudes, and the behaviour towards influenza A/H1N1 and the vaccination among health-care workers (HCWs).MethodsA sample of HCWs was selected from a random sample of non-teaching public hospitals, located in the cities of Naples and Avellino (Italy), received a self-administered anonymous questionnaire including questions about socio-demographic characteristics, knowledge on modes of transmission and preventative measures, attitudes and behaviour relating to influenza A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 24 publications
5
51
1
4
Order By: Relevance
“…As concerns influenza, in a recent Italian study Albano et al demonstrated that healthcare workers are not fully aware of the mode of transmission; HCWs with good knowledge of this issue were those who mostly read pertinent scientific literature [12]. …”
Section: Discussionmentioning
confidence: 99%
“…As concerns influenza, in a recent Italian study Albano et al demonstrated that healthcare workers are not fully aware of the mode of transmission; HCWs with good knowledge of this issue were those who mostly read pertinent scientific literature [12]. …”
Section: Discussionmentioning
confidence: 99%
“…When the risk of infection is thought to be high, acceptance and compliance with interventions to prevent infection are generally higher. 126 Compliance was reported to be high during the initial phase of the H1N1-pdm09 pandemic, when risk perception was high, but it later decreased when healthcare workers thought that the pandemic was less severe than initially estimated. 121 In countries that have experienced epidemics such as SARS, mask wearing is more acceptable, but it is not commonplace in countries such as the UK, US, and Australia.…”
Section: Transmission Modesmentioning
confidence: 99%
“…Positive perception towards health can promote better hygiene practices. Study in Italy found that individuals who consider themselves at risk are adherence to preventive practices against Influenza (Albano, Matuozzo, Marinelli, & Di Giuseppe, 2014). Therefore, the perception of barriers to practice proper hand washing among DM should be stopped in order to increase awareness to adopt it as a healthy habit and enable them to become effective peer educator (Mearkle, Houghton, Bwonya, & Lindfield, 2016).…”
Section: Discussionmentioning
confidence: 99%